2020
DOI: 10.1097/olq.0000000000001261
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Prevalence by Age and Correlates of Infection Among Pregnant Women

Abstract: Chlamydia was detected in 7.4% of >13,500 pregnant women tested at an academic center in Alabama. Age less than 30 years was strongly associated with infection in adjusted models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The prevalence of C. trachomatis infection was higher among younger age groups (Table 1) as previously described 7,13,34,36–38,46,47 . Our results (7.2% in women under 25 years and 2.5% in women between 25 and 29 years old) are similar to rates in large cohorts of pregnant women in the Netherlands and Germany and women of reproductive age in France, 33,37,46 but lower than those found in pregnant women in Birmingham, USA (14.6% and 4.3%, respectively) 20 . Rours et al found screening of under‐30‐year‐old pregnant women to be cost‐effective, 33 and the prevalence in the 25–29 age group in our study suggest that screening in Gipuzkoa for pregnant women under 30 years old should be maintained, in line with recommendations of the Australian government 46 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The prevalence of C. trachomatis infection was higher among younger age groups (Table 1) as previously described 7,13,34,36–38,46,47 . Our results (7.2% in women under 25 years and 2.5% in women between 25 and 29 years old) are similar to rates in large cohorts of pregnant women in the Netherlands and Germany and women of reproductive age in France, 33,37,46 but lower than those found in pregnant women in Birmingham, USA (14.6% and 4.3%, respectively) 20 . Rours et al found screening of under‐30‐year‐old pregnant women to be cost‐effective, 33 and the prevalence in the 25–29 age group in our study suggest that screening in Gipuzkoa for pregnant women under 30 years old should be maintained, in line with recommendations of the Australian government 46 .…”
Section: Discussionsupporting
confidence: 88%
“…A coverage of above 70% of the target population has been considered acceptable in prevalence studies, a figure that has been reached in the present screening 17 . Other pregnancy screening programs have reported similar rates: 60‐70% in ten USA states, 85% in Toronto (Canada), and 77% in Birmingham (USA) 18–20 . Coverage in STI screening during pregnancy tends to be higher than in other population‐based screening programs, given that the testing is offered as part of a set of medical and healthcare services.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our study reveals a large hidden disease burden of undiagnosed CT among Chinese women. Compared with the CT prevalence in countries such as United States (7.4% in pregnant women during 2014–2017) [ 22 ] and low- and middle-income countries in Asia (0.8% in 2012–2015) [ 23 ], our study population had a higher prevalence: 6.7% for pregnant women, 8.2% for gynecology clinic attendees, and 5.9% for infertility clinic attendees. We also note a relatively high prevalence in women from Shenzhen (10.1% in sexual and reproductive health clinics in 2018) [ 24 ], Taizhou (10.2% in gynecology outpatients during 2013–2018), and Beijing (5.9% in outpatient clinic attendees during 2013–2016) [ 16 ].…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, other studies report that the number of Chlamydia infections is higher than expected, evidencing that screening must be implemented regardless of the estimated prevalence [ 42 , 43 ]. In addition, several studies have reported that Chlamydia is more prevalent in adolescent and young women due to their higher biological susceptibility and behavior, supporting the implementation of a screening program for Chlamydia, at least in women who are 15–24 years old [ 44 , 45 , 46 , 47 ]. This evidence highlights the importance of developing a screening program in all of the developed countries, covering all sexually active individuals, and re-testing—due to possible reinfections—in order to treat the positive patients in a timely manner, to control the spread of Chlamydia infection in the population, and to avoid the morbidity of those infected [ 4 ].…”
Section: Chlamydia Trachomatis Epidemiology and Screening Pr...mentioning
confidence: 99%